Development of the Work Intention Inventory Short‐Form. Issue 1 (January 2015) - Nimon, Kim; Zigarmi, Drea
Abstract The Work Intention Inventory (WII: Zigarmi, Nimon, Houson, Witt, & Diehl, 2012) was designed to assess five measures of work intention. Measuring employee intentions is important to consider when evaluating outcomes associated with employee engagement or work passion as research indicates intentions are strong predictors of behavior. Following scale reduction procedures developed by Stanton, Sinar, Balzer, and Smith (2002), we used inter‐item covariance matrices from Zigarmi et al. (2012) and data resulting from the field test of the WII‐Short Form (WII‐SF) in a manufacturing company to develop a short form of the WII and provide initial evidence of construct validity. There is preliminary evidence to indicate that the WII‐SF may offer practitioners and researchers an efficient way to reliably and validly assess employee work intentions